Plant-Based ZnO Nanoparticles for Green Nanobiocontrol of a Highly Virulent Bacterial Leaf Blight Pathogen: Mechanistic Insights and Biocompatibility Evaluation - Preeda Chanthapong; Duangkamol Maensiri; Paweena Rangsrisak; Thanee Jaiyan; Kanchit Rahaeng; Atcha Oraintara; Kunthaya Ratchaphonsaenwong; Jirawat Sanitchon; Piyada Theerakulpisut; Wuttipong Mahakham (Nanomaterials)
Bacterial leaf blight (BLB), caused by Xanthomonas oryzae pv. oryzae (Xoo), poses a serious threat to rice cultivation. This study presents the green synthesis of zinc oxide nanoparticles (ZnO NPs) using an aqueous leaf extract of the medicinal plant Centella asiatica (L.) Urban and evaluates their potential as dual-function nanopesticides. The synthesized CA-ZnO NPs exhibited high crystallinity, a hexagonal to quasi-spherical morphology, and nanoscale dimensions (~22.5 nm), as confirmed by UV–Vis spectroscopy, XRD, FTIR, SEM, TEM, and SAED analyses. These nanoparticles demonstrated potent antibacterial activity against a highly virulent, field-derived Thai Xoo strain, with a minimum inhibitory concentration (MIC) of 8 µg/mL. Mechanistic investigations revealed substantial membrane disruption, intracellular nanoparticle penetration, and elevated reactive oxygen species (ROS) generation in treated cells. Cytotoxicity testing using human dermal fibroblasts (HDFs) revealed excellent biocompatibility, with no statistically significant reduction in cell viability at concentrations up to 500 µg/mL. In contrast, viability markedly declined at 1000 µg/mL. These findings underscore the selective antibacterial efficacy and minimal mammalian cytotoxicity of CA-ZnO NPs. Overall, CA-ZnO NPs offer a promising green nanopesticide platform that integrates potent antibacterial activity with biocompatibility, supporting future applications in sustainable crop protection and biomedical nanotechnology.